Employee development managament: An imperative for Industy 5.0 - Marković Mirko; Tomašević-Nešić Ana; Gardašević Jovana (Ekonomija: teorija i praksa)
Employee development represents both an imperative and a necessity for organizations strategically planning their business ventures and caring for their future, especially during the transition to Industry 5.0, where employees' knowledge, abilities, and motivations create a comparative advantage and bring significant benefits to organizations. The paper examines the developmental opportunities for employees through theoretical analysis and practical research, considering their subjective assessments, as well as managerial factors influencing development. The research was conducted on a sample of 480 employees, using standardized questionnaires. The first questionnaire measured developmental experiences using the Developmental Experiences Description Scale (Wayne et al., 1997), while the management style was assessed using the Supportive and Non-Controlling Supervision Scale (Oldham & Cummings, 1996). The results indicate modest assessments of development opportunities but suggest that a non-directive management model may have a positive impact on employee development.